An improved ant colony optimization algorithm and its applications to limit analysis of frame structures. Issue 11 (2nd November 2019) - Greco, A.; Pluchino, A.; Cannizzaro, F.
ABSTRACT: This article presents a modified ant colony systems approach, which allows reduction of the computational effort needed to converge to the optimal solution of a given engineering problem. The proposed algorithm is applied to the evaluation of the plastic load and failure modes of planar frames. The approach is based on the generation of elementary collapse mechanisms and on their linear combination, aimed at minimizing the collapse load factor. Many applications have been performed on frames of different sizes subjected to seismic load scenarios, i.e. permanent vertically distributed and variable concentrated forces at each floor. The values of the collapse load obtained with the proposed algorithm have been compared with those obtained by means of other optimization algorithms and nonlinear pushover analysis. An extended performance comparison between the proposed procedure and standard ant colony system algorithms shows the expected improvements in terms of a great reduction in the computational effort.